Depiction of Varuna on the Kakshasasna - Temples of India Project Team (Jio Institute, 2024)
Varuna is depicted on the kakshasasna (seat back), of the Undeshwar Temple, alongside his vehicle, the Makara (crocodile). He holds a pasha (noose) in his upper right hand and a pushpa (flower) in his upper left hand. In his lower left hand, he carries a kamandalu (water pot), while his lower right hand is extended in the Varada hasta (hand gesture of conferring a boon) gesture.